Acute myeloid/T‐lymphoblastic leukaemia (AMTL): a distinct category of acute leukaemias with common pathogenesis in need of improved therapy. (14th February 2018) - Gutierrez, Alejandro; Kentsis, Alex
Summary: Advances in the classification of acute leukaemias have led to improved outcomes for a substantial fraction of patients. However, chemotherapy resistance remains a major problem for specific subsets of acute leukaemias. Here, we propose that a molecularly distinct subtype of acute leukaemia with shared myeloid and T cell lymphoblastic features, which we term acute myeloid/T‐lymphoblastic leukaemia (AMTL), is divided across 3 diagnostic categories owing to variable expression of markers deemed to be defining of myeloid and T‐lymphoid lineages, such as myeloperoxidase and CD3. This proposed diagnostic group is supported by (i) retained myeloid differentiation potential during early T cell lymphoid development, (ii) recognition that some cases of acute myeloid leukaemia (AML) harbour hallmarks of T cell development, such as T‐cell receptor gene rearrangements and (iii) common gene mutations in subsets of AML and T cell acute lymphoblastic leukaemia (T‐ALL), including WT1, PHF6, RUNX1 and BCL11B . This proposed diagnostic entity overlaps with early T cell precursor (ETP) T‐ALL and T cell/myeloid mixed phenotype acute leukaemias (MPALs), and also includes a subset of leukaemias currently classified as AML with features of T‐lymphoblastic development. The proposed classification of AMTL as a distinct entity would enable more precise prospective diagnosis and permit the development of improved therapies for patients whose treatment is inadequate with current approaches.